Legumain promotes tubular ferroptosis by facilitating chaperone-mediated autophagy of GPX4 in AKI - Chuan’ai Chen; Dekun Wang; Yangyang Yu; Tianyuan Zhao; Ningning Min; Yan Wu; Lichun Kang; Yong Zhao; Lingfang Du; Mianzhi Zhang; Junbo Gong; Zhujun Zhang; et al. (2021)
Abstract Legumain is required for maintenance of normal kidney homeostasis. However, its role in acute kidney injury (AKI) is still unclear. Here, we induced AKI by bilateral ischemia-reperfusion injury (IRI) of renal arteries or folic acid in lgmn WT and lgmn KO mice. We assessed serum creatinine, blood urea nitrogen, histological indexes of tubular injury, and expression of KIM-1 and NGAL. Inflammatory infiltration was evaluated by immunohistological staining of CD3 and F4/80, and expression of TNF-α, CCL-2, IL-33, and IL-1α. Ferroptosis was evaluated by Acsl4, Cox-2, reactive oxygen species (ROS) indexes H 2 DCFDA and DHE, MDA and glutathione peroxidase 4 (GPX4). We induced ferroptosis by hypoxia or erastin in primary mouse renal tubular epithelial cells (mRTECs). Cellular survival, Acsl4, Cox-2, LDH release, ROS, and MDA levels were measured. We analyzed the degradation of GPX4 through inhibition of proteasomes or autophagy. Lysosomal GPX4 was assessed to determine GPX4 degradation pathway. Immunoprecipitation (IP) was used to determine the interactions between legumain, GPX4, HSC70, and HSP90. For tentative treatment, RR-11a was administrated intraperitoneally to a mouse model of IRI-induced AKI. Our results showed that legumain deficiency attenuated acute tubular injury, inflammation, and ferroptosis in either IRI or folic acid-induced AKI model. Ferroptosis induced by hypoxia or erastin was dampened in lgmn KO mRTECs compared with lgmn WT control. Deficiency of legumain prevented chaperone-mediated autophagy of GPX4. Results of IP suggested interactions between legumain, HSC70, HSP90, and GPX4. Administration of RR-11a ameliorated ferroptosis and renal injury in the AKI model. Together, our data indicate that legumain promotes chaperone-mediated autophagy of GPX4 therefore facilitates tubular ferroptosis in AKI.